Comparative Study of Relative Peripheral Refraction in Children With Different Degrees of Myopia - Xiaoli, Lu; Xiangyue, Zheng; Lihua, Lian; Yuting, Huang; Chuni, Lin; Yujie, Xia; Zhao, Wang; Xiaoyi, Yu (Frontiers in Medicine, 2022)
Purpose To investigate the difference in the retinal refraction difference value (RDV) using multispectral refractive topography (MRT). Methods Ninety myopic participants, who met the enrolment requirements, were examined with an automatic optometer after mydriasis. According to the value of the spherical equivalent (SE), the participants were divided into Emmetropia group (E, +0.5D < SE < −0.5D), Low Myopia (LM, −0.5D < SE ≤ −3D), and Moderate and high Myopia (MM, −3D < SE ≤ −10D). The ocular biological parameters were detected by optical biometrics (Lenstar 900, Switzerland), including axial length (AL), lens thickness (LT), and keratometry (K1, K2). Furthermore, the MRT was used to measure the retinal RDV at three concentric areas, with 15-degree intervals from fovea into 45 degrees (RDV-15, RDV 15–30, and RDV 30–45), and four sectors, including RDV-S (RDV-Superior), RDV-I (RDV-Inferior), RDV-T (RDV-Temporal), and RDV-N (RDV-Nasal). Results In the range of RDV-15, there was a significant difference in the value of RDV-15 between Group E (−0.007 ± 0.148) vs. Group LM (−0.212 ± 0.399), and Group E vs. Group MM (0.019 ± 0.106) (P < 0.05); In the range of RDV 15–30, there was a significant difference in the value of RDV 15–30 between Group E (0.114 ± 0.219) vs. Group LM (−0.106 ± 0.332), and Group LM vs. Group MM (0.177 ± 0.209; P < 0.05); In the range of RDV 30–45, there was a significant difference in the value of RDV 30–45 between Group E (0.366 ± 0.339) vs. Group LM (0.461 ± 0.304), and Group E vs. Group MM (0.845 ± 0.415; P < 0.05); In the RDV-S position, there was a significant difference in the value of RDV-S between Group LM (−0.038 ± 0.636) and Group MM (0.526 ± 0.540) (P < 0.05); In the RDV-I position, there was a significant difference in the value of RDV-I between Group E (0.276 ± 0.530) vs. Group LM (0.594 ± 0.513), and Group E vs. Group MM (0.679 ± 0.589; P < 0.05). In the RDV-T position, there was no significant difference in the value of RDV-T among the three groups. In the RDV-N position, there was a significant difference in the value of RDV-N between Group E (0.352 ± 0.623) vs. Group LM (0.464 ± 0.724), and Group E vs. Group MM (1.078 ± 0.627; P < 0.05). The RDV analysis in all directions among the three groups showed a significant difference between RDV-S and RDV-I in Group LM (P < 0.05). Moreover, the correlation analysis showed that SE negatively correlated with AL, RDV 30–45, RDV-S, RDV-I, and RDV-N. Conclusions In this study, there was a significant difference in the value of RDV among Group E, Group LM, and Group MM, and the value of RDV in Group MM was the highest on the whole. In the range of RDV 30–45, there was a growing trend with the increase in the degree of myopia among the three groups. Furthermore, the SE negatively correlated with AL, RDV 30–45, RDV-S, RDV-I, and RDV-N.